Comprehensive Budget Preparation for Noga Coffee Micro, Small and Medium Enterprises in Kartasura - Fatma Rinjaani Mariska; Ahmad Ghalih Rais Pradana; Dina Faozah; Danantika Widyastuti; Ika Yoga (ADM : Jurnal Abdi Dosen dan Mahasiswa, 2024)
This research aims to compile a comprehensive budget for Noga Coffee MSMEs in Kartasura, as an effort to increase financial efficiency and support business sustainability. Budget preparation is categorized as important for MSMEs, especially in facing operational obstacles and market competition. The methods used in this research include direct Qualitative approach,and observation, interviews with management, and analysis of financial reports.